PENGARUH MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN ALIH DAYA (OUTSOURCING) DI PALEMBANG SQUARE - M. Fadil Hidayat; Badia Perizade; Supardi A. Bakri (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2014)
The purpose of this research is to study about the effect of motivation on job satisfaction of outsourcing employee in Palembang Square. Motivation is proxied by physiological necessity, safety necessity, social necessity, admition necessity, and actualization necessity. Meanwhile, job satisfaction is proxied by mental challenging work, proper salary and wages, supporting work condition, supporting work partner, suitability of personality with the work. Research object is outsourcing employees in Palembang Square that is divided into six work unit which obtained 196 outsourcing employee as a sample. Method for collecting data used are questionnaire and interview. The collected data are tested by validity test, realibility test, normality test, partial test, simple regression analysis, and cross tabulation. This research results shows that motivation variable affected positively and significantly on job satisfaction of outsourcing employee in Palembang Square. According to analysis result, offered some suggestions such as Management of Palembang Square should give training and development effectively, give appreciation to employee who have good performance and maintain the existing work condition.Keywords : Motivation and Job Satisfaction